The relativity of HR systems: conceptualising the impact of desired employee contributions and HR philosophy. (1st September 2004) - Lepak, David P.; Marrone, Jennifer A.; Takeuchi, Riki
In this paper, we offer a framework for conceptualising and investigating the relativity of human resource (HR) systems across organisations and some of the reasons behind this relativity. We do so by extending the behavioural perspective in strategic HR management research and argue that two variables, HR philosophy and desired employee contributions, play an instrumental role in organisational choices regarding the types of HR policies used to manage employees within and across organisations. We propose that the dimensions of desired employee contributions determine which sets of HR policies are feasible while HR philosophy governs the specific choices of HR policies within firms. Future directions and implications are also discussed.